Determinants of Consumer Purchasing Decisions for Vanilla Products (A Case Study of Vanilla Global Indonesia) - Sulung Anugerah Sahara; Erlin Widya Fatmawati; Endro Puji Astoko (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
Vanilla is a high-value commodity with significant demand in domestic and international markets, making consumer behavior an essential aspect of its marketing strategy. Understanding the factors that drive purchasing decisions can help businesses like Vanilla Global Indonesia optimize their offerings and marketing efforts to meet consumer needs effectively. The purpose of this research is to determine the characteristics of consumers of vanilla products at Vanilla Global Indonesia and to find out what factors influence the decision to purchase vanilla products at Vanilla Global Indonesia. This research was carried out in 2023 with 50 respondents from consumers who made purchase decisions at Vanilla Global Indonesia, with an age qualification of more than 17 years. Regression analysis with classical assumption tests is used in this study to see the variables of quality, price, packaging, and promotion, and their influence on purchasing decisions for Indonesian global vanilla products. This research shows that 20 people came from Korea, and the number of customer respondents with a D3 education level is as many as 20 people, with customers having a chef job level of 21 people. This analysis showed that quality, price, packaging, and promotion positively affect purchase decisions, which means that if the variable increases, then the consumer's purchasing decision for Vanilla will also increase. The product quality variable significantly influences consumer purchasing decisions for Vanilla, with a coefficient of 0.470.